2000
DOI: 10.1128/aac.44.4.920-928.2000
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Phenotypic Drug Susceptibility Assay for Human Immunodeficiency Virus Type 1

Abstract: Although combination antiretroviral therapy has resulted in a considerable improvement in the treatment of human immunodeficiency virus (HIV) type 1 (HIV-1) infection, the emergence of resistant virus is a significant obstacle to the effective management of HIV infection and AIDS. We have developed a novel phenotypic drug susceptibility assay that may be useful in guiding therapy and improving long-term suppression of HIV replication. Susceptibility to protease (PR) and reverse transcriptase (RT) inhibitors is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

13
482
1
2

Year Published

2000
2000
2007
2007

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 602 publications
(498 citation statements)
references
References 56 publications
13
482
1
2
Order By: Relevance
“…By itself, it causes low-level resistance to NFV and IDV. However, in the presence of D30N or M46I it causes high-level NFV resistance (Petropoulos et al 2000) as reported in 1 child. The M46L was reported in 2 children; it contributes resistance to each of the PIs except possibly SQV and has been commonly reported during therapy with IDV, RTV, APV, and NFV (Condra et al 2000b).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…By itself, it causes low-level resistance to NFV and IDV. However, in the presence of D30N or M46I it causes high-level NFV resistance (Petropoulos et al 2000) as reported in 1 child. The M46L was reported in 2 children; it contributes resistance to each of the PIs except possibly SQV and has been commonly reported during therapy with IDV, RTV, APV, and NFV (Condra et al 2000b).…”
Section: Discussionmentioning
confidence: 98%
“…The Y181C and G190S mutations were reported in 1 child and the other one presented additional resistance mutations at sites A98G and V108I. The Y181C mutation causes a more than 30-fold resistance to NVP and DLV and 2 to 3-fold resistance to EFV (Petropoulos et al 2000). The G190S mutation causes high-level resistance to both NVP and EFV .…”
Section: Discussionmentioning
confidence: 99%
“…The only commercially available fitness assay is a parallel-infection, recombinant-virus, single-cycle RC assay developed by Monogram Biosciences, Inc. (formerly ViroLogic) (15). This assay, which is a variation on Monogram's phenotypic drug susceptibility assay (133), compares test and reference strains in the absence of drug (Fig. 2).…”
Section: Cell Culture Assaysmentioning
confidence: 99%
“…2). An amplicon spanning the p7-p1-p6 cleavage sites in Gag, the entire protease, and part of the reverse transcriptase (codons 1 to 313) is obtained from patient plasma and cloned in bulk into an HIV-1 vector derived from the pNL4-3 infectious molecular clone containing a luciferase reporter gene that replaces part of env (133). Luciferase is expressed upon establishment of infection and is a measure of viral infection (133).…”
Section: Cell Culture Assaysmentioning
confidence: 99%
See 1 more Smart Citation